Production and characterization of chicken IgY for detecting wheat stripe mosaic virus - Santos A.K.A.* (2022)
© 2022, The Author(s), under exclusive license to Sociedade Brasileira de Fitopatologia.In Brazil, wheat (Triticum aestivum) is cultivated mainly in the southern part. The soilborne wheat mosaic disease (SBWMD), caused by the wheat stripe mosaic virus (WhSMV), is one of the most important viruses in the region. Its diagnosis is based mainly on symptoms since molecular techniques are expensive, especially for RNA genomes viruses. However, serological tests using IgY immunoglobulins are highly effective in identifying viruses. This study aimed to produce and characterize a polyclonal antibody capable of interacting with the WhSMV capsid protein. The gene encoding the virus capsid protein was inserted into the expression vector pET-15b; the transformation and expression occurred in Escherichia coli BL21::DE3 in vitro. The recombinant protein was inoculated in laying hens (Gallus gallus domesticus). The anti-WhSMV IgY antibodies were extracted from the chicken yolks. The IgY was the basis for immuno-assays such as indirect Enzyme-linked immunosorbent assay (ELISA) and Western blot, targeting the purified capsid protein or the whole virus. Also, a PCR test was performed with samples of root and leaves of infected plants, confirming the presence of the virus in both tissues. The PCR results were in agreement with the ELISA tests performed with all samples. IgY produced in chickens specifically recognized the purified viral protein and the WhSMV present in the extract from leaves of WhSMV-infected plants.